Cheated : the UNC scandal, the education of athletes, and the future of big-time college sports - Smith, Jay M.; Willingham, Mary (Potomac Books, an imprint of the University of Nebraska Press, 2015)
"Examines athletic-academic corruption at UNC-Chapel Hill and in NCAA athletics"--